SERBIA AND EXPANDED DETERRENCE: EXPERIENCES AND ROADMAPS - Blagojevic, Veljko (The Policy of National Security, 2025)
The strategic concept of extended deterrence emerged in the post-Cold War period by expanding the content of the Cold War concept of nuclear deterrence of the allies of the great powers. Therefore, modern extended deterrence implies the use of all instruments of national power to deter rivals from taking malicious steps against allies or partners. This paper deals with the consideration of the historical experience of the Serbs in the application of this concept, as well as with the analysis of the foreign policy means used and the outcomes of their application. The basic hypothesis of the paper is that during the existence of an independent state, the Serbs applied extended deterrence with support from the diaspora and that this concept should be applied in the future but with an emphasis on so-called soft deterrence. It will examine certain events and processes during the Crimean War (Serbia as a vassal principality), the Chetnik movement and method of warfare (Kingdom of Serbia), and the strategic actions of the Serbs during the wars for the Yugoslav succession, in which patterns of Serbian extended deterrence are characteristic.